Hibriditas dan Keterikatan Sosial: Transformasi Sosial dan Negosiasi Identitas pada Masyarakat Geser di Seram Timur - Aria, Vina; Murwani, Prapti (Universitas Pattimura, 2023)
This study examines the dynamics of cultural hybridity and social belonging among the indigenous Geser community in Eastern Seram, a society undergoing social transformation through intense interactions with external influences such as religion, education, economy, and technology. Employing a cultural ethnographic and reflective sociological approach, the research integrates participatory observation, local narratives, and digital mapping of collective identity. The findings reveal that the identity of the Geser people is not static but continually negotiated through the blending of local customs, cosmopolitan Islam, and modern influences like migration and social media. These processes generate varying senses of belonging and estrangement across social groups, particularly among youth, women, and the diaspora. The study contributes a novel perspective by grounding theories of cultural hybridity within the context of Eastern Indonesia, expanding their theoretical reach within Southeast Asian identity studies. The main conclusion asserts that